Upaya Pengembangan Keterampilan Menulis Puisi Siswa Kelas V SD Dengan Memanfaatkan Media Lingkungan - Paramitha, Putu Elvira Pradnya (Jayapangus Press, 2023)
The use of environmental media in learning to write poetry offers a solution to increase students' interest and ability in writing poetry. Environmental media refers to all aspects around students that can be used as inspiration or learning materials, such as natural beauty, the uniqueness of local culture, and social phenomena that occur around them. The purpose of this study is to find out how the utilization of environmental media in an effort to develop the poetry writing skills of fifth grade elementary school students. This research is a qualitative research, the method of data collection in this research is literature study and observation. The results showed that the utilization of environmental media in teaching poetry writing in elementary school is very important. Nature, local culture, and social life around the school become a rich source of inspiration. This medium has been proven effective in developing students' poetry writing skills, improving vocabulary, emotional expression, and cultural and social understanding. However, there are challenges such as limited resources, rigid curriculum, and variations in students' attention. A holistic approach is needed, combining academics with environmental and cultural sensitivity. Collaboration between schools, teachers, students, parents and communities is needed to overcome these barriers, with creative strategies to integrate environmental media in the learning process effectively.